MORPHOLOGICAL ANALYSIS IN SNOW WHITE AND THE SEVEN DWARFS STORY - Wibowo, Hanafi; Handayani, Vina (Teaching English as Foreign Language, Literature and Linguisticss, 2023)
This research discusses an analysis of the use of word formation in Snow White and The Seven Dwarfs Story. The aims of this research are to find out types of the word formation process in the text. writer. The writer uses classified the data analysis method. To examine the data, researchers used a descriptive qualitative approach. In this research, the researcher collects the data sources from narrative texts that have word formation processes in them. in collecting the data, in this study the researchers will use primary data. The primary data contains data obtained directly by observing or observing the data source. Based on the theories provided, the data are analyzed one by one to know the types of the word formation in Snow White and The Seven Dwarfs Story. Based on the finding and discussion that answered to first problem questions above the researcher were found 84 data of word formation process in Snow White and The Seven Dwarfs Story. There were 42 data of Verb Inflection or 50%, Derivational of Adjective 17 data or 20%, Compounding Word 11 data or 13%, Derivational of Noun 4 data or 5%, Derivational of Verb 2 data or 2%, Derivational of Number 1 data or 1,1%, and there were 0 data of Inflectional of Adjective and Inflectional of Adverb. In this research the word formation process most used was Verb Inflection.